Influence of surgical timing post-neoadjuvant chemotherapy on survival outcomes in breast cancer patients: A comprehensive systematic review and meta-analysis - Dandan Wang; Xiaowei Sun; Wen Sun; Ruoxi Wang; Hong Pan; Wenbin Zhou (Breast)
Background: Increasing evidence supports the use of neoadjuvant chemotherapy (NAC) prior to surgery for breast cancer. However, the optimal timing between NAC and surgery had yet to be fully elucidated. This meta-analysis aims to assess how the optimal interval time (OTT) between NAC and surgery affects outcomes in breast cancer, providing additional evidence for clinical practice and future research. Methods: PubMed, Web of Science and Cochrane Library databases in English were systematically searched for this systematic review. All included studies investigated the variations in surgical timing following NAC and their effects on breast cancer outcomes. The endpoints included the rate of pathological complete response (pCR), overall survival (OS), recurrence free survival (RFS), and disease-free survival (DFS). This study has been registered with PROSPERQ. Results: Eleven eligible studies were identified, encompassing a total of 10,834 cases, all of which received surgery post-NAC. All studies were retrospective in nature. Ultimately, compared to intervals within 4 weeks, patients who underwent surgery>8weeks post-NAC demonstrated a statistically significant worse OS (HR = 1.21, 95 % CI: 1.06–1.40, p = 0.333 for heterogeneity). No significant difference of OS was observed between patients with OTT of 4–8 weeks vs < 4 weeks. Notably, patients with an OTT of 4–8 weeks (HR = 1.18, 95 % CI: 1.10–1.26, I2 = 0.0 %, p = 0.931 for heterogeneity) and>8weeks (HR = 1.21, 95 % CI: 1.13–1.29, I2 = 36.2 %, p = 0.195 for heterogeneity) exhibited decreasing RFS, compared with those with OTTs of<4 weeks. DFS and pCR rates were similar in>8weeks vs < 4 weeks and 4–8weeks vs < 4 weeks. Conclusion: Our systematic review and meta-analysis indicate that the optimal interval following NAC for breast cancer patients might be within four weeks, as delays exceeding eight weeks could be associated with poorer clinical outcomes. However, additional research is necessary to validate these preliminary findings.